2023
DOI: 10.1093/oxfmat/itad021
|View full text |Cite
|
Sign up to set email alerts
|

Is electrostrain >1% in oxygen deficient Na0.5Bi0.5TiO3 a composition effect?

Getaw Abebe Tina,
Gudeta Jafo Muleta,
Gobinda Das Adhikary
et al.

Abstract: For over two decades Na0.5Bi0.5TiO3 (NBT) -based lead-free piezoelectrics have attracted attention due to its ability to exhibit large electric-field driven strain. Compared to the popular Pb(Zr, Ti)O3 (PZT)-based piezoelectrics, which exhibit electrostrain of about 0.3%, the derivatives of NBT-based lead-free piezoelectrics at the ergodic—non ergodic relaxor crossover exhibit larger electric-field driven strain ∼0.45%. In recent years, there has been a concerted effort to increase the maximum electrostrain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…As we are mainly focused on tuning the dimension of piezoceramics, a highly piezoelectric material with wellknown and fixed MPB composition has to be chosen here. The converse piezoelectricity of thickness tuned MPB compositions of PZT, Sn doped BaTiO 3 , KNN, and NBT have already been investigated earlier [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we are mainly focused on tuning the dimension of piezoceramics, a highly piezoelectric material with wellknown and fixed MPB composition has to be chosen here. The converse piezoelectricity of thickness tuned MPB compositions of PZT, Sn doped BaTiO 3 , KNN, and NBT have already been investigated earlier [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…But, the mechanisms such as field induced phase change, field induced transition of material from ergodic to ferroelectric nature, and reversible switching of ferroelastic domains can not be explained only by considering the compositions [6]. 0.74Na 0.5 Bi 0.5 TiO 3 -0.26SrTiO 3 , (KNa)NbO 3 (KNN) and its derivatives and (NaBi)TiO 3 (NBT) have been widely studied by them over a wide composition range and thickness variation [2,[6][7][8]. By performing all of these experiments, they have concluded that the thickness reduction of the bulk piezoceramics can effectively increase their electrostrain by reducing the mutual mechanical clamping between the grains [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation